Trait Preference Coefficients that scale economic weights - Adams, Chris; Byrne, Tim; Cole, Steven (WorldFish, 2024)
Respondent trait preferences (observed preference) were calculated using the 1000minds survey. The expected preference is calculated from the monetary worth of the trait improvement offered in the survey. The observed preferences were divided by the expected preferences to get trait preference coefficients. The trait preference coefficients were then analysed using a principal component analysis followed by a bootstrapped (100,000) k-means (k = 4) clustering to determine trait preference clusters. The mean trait preference coefficient per cluster was then calculated